2004
DOI: 10.1197/jamia.m1525
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Computerized Physician Documentation in a Teaching Hospital: Perceptions of Faculty and Resident Physicians

Abstract: CPD is perceived to have substantial positive and negative impacts on clinical and educational activities and environments. Care should be taken when designing, implementing, and using such systems to avoid or minimize any harmful impacts. More research is needed to assess the extent of the impacts identified and to determine the best strategies to effectively deal with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 26 publications
5
135
0
Order By: Relevance
“…40,41 This may in part be driven by EHR templates designed for easy data extraction for billing and coding, but not for inclusion of a diagnostic or therapeutic rationale connecting the discharge information to the outpatient provider's task. Studies of the VA's EHR have suggested that the practice of copying and pasting notes also leads to both "benign" and "misleading" errors, as well as to a lack of updates regarding patient conditions, and to redundant information, 42 which may point to inherent limits of EHRs compared to paper records. 22 Awareness of the significance of discontinuities in care has been heightened with the recognition that medical error is the third leading cause of death in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 This may in part be driven by EHR templates designed for easy data extraction for billing and coding, but not for inclusion of a diagnostic or therapeutic rationale connecting the discharge information to the outpatient provider's task. Studies of the VA's EHR have suggested that the practice of copying and pasting notes also leads to both "benign" and "misleading" errors, as well as to a lack of updates regarding patient conditions, and to redundant information, 42 which may point to inherent limits of EHRs compared to paper records. 22 Awareness of the significance of discontinuities in care has been heightened with the recognition that medical error is the third leading cause of death in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized documentation is the direct entry of a physicians’ notes into the electronic medical record (EMR) through the intrahospital network, and offers improved legibility and real‐time accessibility 1. Such integrated EMR systems can ensure that a physician's documentation is easier to browse than a traditional paper record; thereby, providing reference for the next examination 2…”
Section: Introductionmentioning
confidence: 99%
“…P.J. Embi et al [38] lament that, these benefits are often coupled with unintended consequences in the actual work practices, such as increased documentation time incompatibility with clinical workflow more interruptions in medical work and system-introduced errors in patients care.…”
Section: Database Management System In the Field Of Medicinementioning
confidence: 99%
“…Embi et al [38] there are some causes of medical errors and one of these is due to different physicians treating the same patient. Not all or only a few physicians can access to all the patient's medical records.…”
Section: Database Management System In the Field Of Medicinementioning
confidence: 99%